Affordances, barriers, and motivations: engagement in research activity by academics at the research-oriented university in Vietnam. Issue 1 (1st January 2016) - Nguyen, Quy; Klopper, Christopher; Smith, Calvin
ABSTRACT: The importance of academics undertaking research and publishing their research results is emphasised by universities. Engagement in research is recognised as an effective means to increase a university's profile. This study applied a qualitative approach to explore affordances, barriers, and motivations towards the engagement in research experienced by academics at one of the leading universities in Vietnam. Nineteen semi-structured interviews were conducted with academics whose academic rank, discipline, qualification, age, and gender are different. A thematic analysis of the data discovered four institutional factors hindering the engagement in research of academics: financial support for research activities (affordance); teaching load (barrier); research collaboration (motivation); and research policy settings and practices (motivation). The findings revealed that a majority of the respondents were aware of the importance of research but their research productivity is still low because of problems related to such institutional factors. The findings are useful in assisting leaders of the investigated university to understand the research motivation of its academics as well as ascertain barriers to which academics are facing that can be overcome through intervention. Such understanding helps them to improve the policy for research across this university which is predicted to enhance the research productivity of all academics.